1994
DOI: 10.1128/jb.176.15.4664-4668.1994
|View full text |Cite
|
Sign up to set email alerts
|

Why does Escherichia coli have two primary pathways for synthesis of glutamate?

Abstract: Escherichia coli has two primary pathways for glutamate synthesis. The glutamine synthetase-glutamate synthase pathway is known to be essential for synthesis at low ammonium concentrations and for regulation of the glutamine pool, but the necessity for glutamate dehydrogenase (GDH) has been uncertain. The results of competition experiments between the wild type and a GDH-deficient mutant during nutrient-limited growth and of direct enzyme measurements suggest that GDH is used in glutamate synthesis when the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 33 publications
10
123
0
1
Order By: Relevance
“…GOGAT can fix ammonium into organic molecules (glutamine, thence glutamate and other compounds) when the external concentration of ammonium is low, and it reduces the concentration of glutamine when that concentration becomes high (Reitzer 1986). Note also that a strain deficient in glutamate dehydrogenase has no observable growth phenotype under usual growth conditions (Reitzer 1986) but that GDH appears to be important during energy-limited growth because, through its use, the cost of biosynthesis is scaled down (Helling 1994). …”
Section: Ammonia Assimilation Pathway In E Colimentioning
confidence: 99%
“…GOGAT can fix ammonium into organic molecules (glutamine, thence glutamate and other compounds) when the external concentration of ammonium is low, and it reduces the concentration of glutamine when that concentration becomes high (Reitzer 1986). Note also that a strain deficient in glutamate dehydrogenase has no observable growth phenotype under usual growth conditions (Reitzer 1986) but that GDH appears to be important during energy-limited growth because, through its use, the cost of biosynthesis is scaled down (Helling 1994). …”
Section: Ammonia Assimilation Pathway In E Colimentioning
confidence: 99%
“…Importantly, parallel metabolic pathways could evolve not only to metabolize qualitatively different nutrient molecules, but also in response to variation in the quantitative availability of nutrients. For example, E. coli has two pathways of glutamate synthesis, one of which can fix ammonium into organic molecules when the external concentration of ammonium is low, while the other plays an important role when the cell is limited for energy, but is not under ammonium restriction (Helling, 1994). Finally, the evolutionary maintenance of compensating isoenzymes in metabolic networks could be explained by selection to increase gene dosage (i.e., to increase flux) (Conant and Wolfe, 2007;Papp et al, 2004), filter nongenetic noise (Kafri et al, 2006), or provide differential regulation of isoforms (Ihmels et al, 2004).…”
Section: Robustness Against Gene Deletions Appears To Be a By-productmentioning
confidence: 99%
“…The expenditure of NADH, ATP and 2-oxoglutarate in this process (Helling, 1994) would drive the utilization/oxidation of succinate and glucose-carbon. It has been shown that optimization of energy flow requires the functioning of energy-dissipating reactions such as the cycling of glutamine (Stucki, 1980;Tempest, 1978 ;Mora, 1990; Fig.…”
Section: Discussionmentioning
confidence: 99%